Effect of Topical Aromatherapy Turmeric Oil to Pruritus Scale on Chronic Kidney Disease Patients - Rysida Ma’rifaul Khoirot; Kusnanto Kusnanto; Suprajitno Suprajitno (STIKes Patria Husada Blitar, 2019)
Introduction : A large number of patients with chronic kidney disease suffer from uremic pruritus, which adversely affects the quality of life and comfort of patients with a potential psychological, functional and social impact, which results in increased morbidity. The purpose of this study was to determine the effect of the administration of turmeric essential oil aromatherapy which was applied topically pruritus, comfort and quality of life of CKD patients.Methods : This study used a quasi-experimental design with 2 groups (intervention and control), conducted in CKD patients receiving hemodialysis therapy. A total sample of 72 respondents with the division of each group of 36 people. The intervention was carried out independently by the patient for 2 weeks. Measurement using 5-D pruritus scale questionnaire.Results : This study showed a decrease in pruritus scale in 51 respondents (70.8%) after 2 weeks of therapy. Independent t statistical test obtained a significance value of 0.046 (p <0.05).Conclusion: Topical aromatherapy of turmeric oil affects pruritus scale on patients with chronic kidney disease who experience uremic pruritus.